Negative emotions in community-dwelling adults with prediabetes and hypertension. Issue 4 (April 2020) - Zhuang, Qianling; Wu, Lirong; Ting, Wang; Jie, Lin; Zou, Jingying; Du, Jiangang
Objective: The purpose of this study was to investigate negative emotions and factors related to the risk of mental disorders in individuals with prediabetes and hypertension. Methods: A total of 504 community-dwelling adult men and women in Suzhou, China, were enrolled and questionnaires used to obtain sociodemographic data, anxiety and depression scores, and current status of common metabolic indicators, including blood glucose level and blood pressure. Results: Anxiety and depression scores in participants with prediabetes and hypertension were significantly higher than those in participants with normal blood glucose levels and normal blood pressure. Correlation analysis revealed that age, sex, smoking, duration of disease, physical activity, blood pressure and fasting plasma glucose levels were key factors accelerating the progression to both anxiety and depression in all participants. Conclusions: More attention should be paid to negative emotions in individuals with prediabetes and hypertension. These findings could help to inform health providers in developing interventions for this population.